2023
DOI: 10.30773/pi.2022.0327
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Seizure Normalizes Motor Deficits and Induces Autophagy Signaling in the MPTP-Induced Parkinson Disease Mouse Model

Abstract: Objective Electroconvulsive seizure (ECS) is a potent treatment modality for various neuropsychiatric diseases, including Parkinson disease (PD). Recent animal studies showed that repeated ECS activates autophagy signaling, the impairment of which is known to be involved in PD. However, the effectiveness of ECS on PD and its therapeutic mechanisms have not yet been investigated in detail.Methods Systemic injection of a neurotoxin 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine hydrochloride (MPTP), which destroys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 71 publications
0
0
0
Order By: Relevance
“…The reported effects were similar to the ones observed with TMS and tDCS, namely the improvement of motor deficits, the preservation of dopamine neurons, and increases in NFs. Intriguingly, one study [88] found evidence that ECT may impact autophagy pathways in PD, although it is unclear whether this finding would translate to human patients. Considering that other forms of non-invasive neuromodulations are likely to offer similar benefits based on the studies reviewed here, while being associated with fewer risks, ECT may be less preferable in clinical practice than other forms of non-invasive neuromodulation.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported effects were similar to the ones observed with TMS and tDCS, namely the improvement of motor deficits, the preservation of dopamine neurons, and increases in NFs. Intriguingly, one study [88] found evidence that ECT may impact autophagy pathways in PD, although it is unclear whether this finding would translate to human patients. Considering that other forms of non-invasive neuromodulations are likely to offer similar benefits based on the studies reviewed here, while being associated with fewer risks, ECT may be less preferable in clinical practice than other forms of non-invasive neuromodulation.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Autophagy. Huh, et al [88] investigated the role of ECT in autophagy in the MPTP mouse model and found that after two weeks of ECT treatment (once a day, three times a week), mice showed an improvement in motor deficits; increased count of TH+ neurons in the SNc; and the normalization of LC3-II levels in the PFC, striatum, and midbrain. LC3-II is an autophagy marker that has been shown to be dysregulated in PD [89] and was found to be modulated by tDCS [17], as reported above.…”
Section: Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation